1997
DOI: 10.1063/1.473393
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the dissociation of dimethyl sulfoxide following absorption at 193 nm

Abstract: We have studied the photodissociation of dimethyl sulfoxide, DMSO-h 6 and DMSO-d 6 , at 193 nm using the technique of photofragment translational spectroscopy with a tunable vacuum ultraviolet product probe provided by undulator radiation on the Chemical Dynamics Beamline at the Advanced Light Source. In contrast to previous investigations we have found the dissociation to proceed via a stepwise mechanism involving multiple reaction channels. The primary dissociation, S-C bond cleavage to eliminate a methyl ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
72
3

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(93 citation statements)
references
References 19 publications
18
72
3
Order By: Relevance
“…The first studies of the 193 nm photolysis using laser-induced fluorescence ͑LIF͒ detection of SO and resonance-enhanced multiphoton ionization ͑REMPI͒ of CH 3 suggest a concerted decomposition, 7 but a subsequent molecular beam photofragmentation experiment using photoionization mass spectrometric detection observes the CH 3 SO fragment and points to a stepwise process in which the CH 3 SO fragment dissociates if it contains sufficient energy. 8 Another photofragment measurement 9 finds that about 53% of the CH 3 SO fragments dissociate in the 193 nm photolysis, in agreement with the methyl yield of 1.4 Ϯ0.2 obtained using a diode laser to probe the methyl products of the 193 nm photolysis. 10 Our results complement the data from the short wavelength photolysis and allow us to explore the role of the initial electronic state by exciting either the *←n(d←n) transition at 210 nm or the *←n transition at 222 nm.…”
Section: Introductionmentioning
confidence: 62%
“…The first studies of the 193 nm photolysis using laser-induced fluorescence ͑LIF͒ detection of SO and resonance-enhanced multiphoton ionization ͑REMPI͒ of CH 3 suggest a concerted decomposition, 7 but a subsequent molecular beam photofragmentation experiment using photoionization mass spectrometric detection observes the CH 3 SO fragment and points to a stepwise process in which the CH 3 SO fragment dissociates if it contains sufficient energy. 8 Another photofragment measurement 9 finds that about 53% of the CH 3 SO fragments dissociate in the 193 nm photolysis, in agreement with the methyl yield of 1.4 Ϯ0.2 obtained using a diode laser to probe the methyl products of the 193 nm photolysis. 10 Our results complement the data from the short wavelength photolysis and allow us to explore the role of the initial electronic state by exciting either the *←n(d←n) transition at 210 nm or the *←n transition at 222 nm.…”
Section: Introductionmentioning
confidence: 62%
“…Previous studies [8][9][10] have used laser photofragmentation at 193 nm (6.425 eV) to study the dissociation of DMSO, and have shown that DMSO undergoes a stepwise dissociation with the main dissociation channel (CH 3 ) 2 SO + hv ! CH 3 SO + CH 3 then CH 3 SO !…”
Section: Introductionmentioning
confidence: 99%
“…Photodissociation via the electronic σ n 'n and π n 'n transitions at 210 and 222 nm (5.90 and 5.58 eV), respectively, have also been shown to release the primary products CH 3 and SO [2]. It has been established from these experiments [2,4,[26][27][28][29][30]] that most of the other possible fragments require extensive nuclear rearrangements that make their production unlikely. Most of these reports suggest that DMSO photolysis proceeds through initial loss of one methyl group at low energies followed by secondary decomposition of CH 3 SO to produce the second methyl group and SO fragments rather than a direct three-body fragmentation to release two methyl groups and SO as primary products.…”
Section: High Resolution Studiesmentioning
confidence: 97%
“…2). Since it is very unlikely that the parent molecule produces SO 2 on photodissociation [4,[26][27][28][29][30], these are attributed to residual SO 2 , which is used for wavelength calibration. To the best of our knowledge, this is the first report of an extended vibronic band system associated with the e 1 Π-X 3 Σ À transition.…”
Section: High Resolution Studiesmentioning
confidence: 99%
See 1 more Smart Citation